Protocol: How to deal with Partial Least Squares (PLS) research in Operations Management. A guide for sending papers to academic journals - Juan A. Marin-Garcia; Rafaela Alfalla-Luque (WPOM : Working Papers on Operations Management)
This work protocol form part of a three-phase publication (Marin-Garcia, 2019). Its objective is to establish a work procedure to answer these questions: 1) in which journals have articles about Operations Management with Partial Least Squares (PLS) been published?; 2) Do the results of previous reviews on this topic still prevail based on the very limited set of journals that it have been conducted (and before substantial modifications were made to report methods of PLS-based studies)?; 3) Do recent articles fulfil report recommendations; 4) What kind of measurement model has been considered for the constructs most frequently used in the selected articles?; 5) What are the usual R2 values in the cross-sectional studies represented in the selected articles?; 6) Within what statistical power range do the relations analysed with PLS fall?